2019
DOI: 10.22270/jddt.v9i4-s.3318
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Widely Used Unani Drug Asl-Us-Soos (Glycyrrhiza glabra Linn.): A Systematic Review

Abstract: Plants have been one of the important sources of therapeutics or other human health benefits  since the beginning of human civilization throughout history. Currently, there is increasing awareness and general acceptability of the use of herbs, as a medicines, health products, pharmaceuticals, food supplements, cosmetics etc. Traditional system of medicine including Ayurveda, Unani, and Siddha etc. contributed in Health care dealing worldwide. The Unani system of medicine (USM) is an age old system of medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Glabridin prevents glucose intolerance and ensures maximum glucose utilization by translocation of GLUT-4 using Adenosine Mono Phosphate Protein Kinase AMPK [56]. Glycyrrhizin enhances the level of glycohaemoglobin, cholesterol, and triglyceride by reducing serum insulin level and pancreatic islet cell numbers [14]. Thus, licorice can play a crucial role in insulin resistance-related illnesses.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Glabridin prevents glucose intolerance and ensures maximum glucose utilization by translocation of GLUT-4 using Adenosine Mono Phosphate Protein Kinase AMPK [56]. Glycyrrhizin enhances the level of glycohaemoglobin, cholesterol, and triglyceride by reducing serum insulin level and pancreatic islet cell numbers [14]. Thus, licorice can play a crucial role in insulin resistance-related illnesses.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…The methanolic extract was found to be a potent anti-oxidant with a maximum scavenging effect of 67.22% at a concentration of 500 μg/ml [120]. The IC 50 calculated for it was 359.45 μg/ml [14]. Phenolic contents present in the ethanolic extracts such as glabridin, hispaglabridin A, and 30-hydroxy-40-methylglabridin-all have anti-oxidant activity through free radical scavenging, hydrogen-donating, metal ion chelating, and reducing abilities.…”
Section: Anti-oxidant Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycyrrhiza glabra has been shown to inhibit SOG-2 [219] Glycyrrhizin has shown steroid-like antiinflammatory activity similar to hydrocortisone due to its inhibition of phospholipase A2 activity[220]. Hashem A. et al [20] showed that licorice was more effective and safer than ranitidine in wound healing. Licorice shows strong anti-ulcer activity and has been shown to be safer in liver and kidney function compared to the standard commercial drug.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) These plants are considered as ecological health marker. (3,4) The drugs derived from medicinal plants are known as herbal drugs or phytomedicines which have been used for treating several health related problems since ancient times. (5) The principal phytochemicals of medicinal plants are alkaloids, phenols, tannins and flavonoids which are associated with several therapeutic properties like anti-inflammatory, anti-bacterial, anti-viral, hepatoprotective, analgesic etc.…”
Section: Introductionmentioning
confidence: 99%